Î±-Lipoic acid inhibit the decrease of collagen deposition in ultravioled B-irradiated cultured normal human skin fibroblasts cell culture - Yohanes Widodo Wirohadidjojo, Arum Krismi Satiti Retno Pudjiati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Repeated ultraviolet B (UVB) irradiation on human skin has been considered to be responsible in premature agingprocess because UVB has been proved to inhibit collagen deposition and accelerates collagen degradation. Clinicalstudies showed that topical usage of 5% Î±-lipoic acid (ALA) improved the clinical appearance of photoaged skin.However, the effect of ALA on collagen deposition and degradation in UVB-irradiated normal human skin fibroblastsculture has not been reported. The aim of the study was to investigate the effect of ALA on collagen deposition anddegradation in UVB-irradiated cultured normal human skin fibroblasts. Culture of normal human skin fibroblasts weretreated with 0, 125, 250, 500 Î¼M ALA diluted in complete Dulbeccoâs Modified Eagleâs Medium (DMEM) andirradiated with 300 mJ/cm2 UVB. The mean collagen deposition and degradationâs level were measured by Siriusred assay and read with spectrophotometer at Î» 550 nm. Mean difference of collagen deposition as expressed byoptical density (OD) between normal human skin fibroblasts cell after UVB irradiation and without UVB irradiationwas analyzed by Wilcoxon signed-ranks test and Friedman test, while mean difference collagen degradation wasanalyzed by one way analysis of variance (ANOVA) and paired t test with 95% confidence level (p<0.05). Theresults showed that ALA 125 Î¼M inhibited the decrease of collagen deposition significantly (p<0.05), though higherconcentrations did not. However, ALA did not inhibit collagen degradation increment (p>0.05). In conclusion, ALAinhibited the decrease of collagen deposition, but did not inhibit collagen degradation in UVB-irradiated normalhuman skin fibroblasts culture.Key words: Î±-lipoic acid - collagen - human skin - fibroblasts â UVB - irradiation